Risk factors of osteonecrosis in patients with systemic lupus erythematosus: a meta-analysis - Zhou, Xiang; Chai, Yijie (Frontiers in Medicine, 2025)
BackgroundThis study aimed to explore risk factors for osteonecrosis in patients with systemic lupus erythematosus by meta-analysis.MethodsPubMed, Embase, Web of Science, and Cochrane Library were searched for case–control/cohort studies on the occurrence of osteonecrosis in patients with systemic lupus erythematosus from the time the database was created until 1 December 2024. Data were analyzed using Stata 15.0, and the quality of the included studies was evaluated using the NOS score.ResultA total of 14 articles, including 3,890 patients, were included in the study, and the meta-analysis indicates that younger age in SLE patients [SMD = −0.23, 95% CI (−0.39, −0.06)], diabetes mellitus [OR = 1.78, 95% CI (1.03, 3.09)], hypertension [OR = 1.33, 95% CI (1.03, 1.72)], arthritis [OR = 1.57, 95% CI (1.24, 2.00)], Raynaud’s phenomenon [OR = 1.76, 95% CI (1.35, 2.30)], and cyclophosphamide use [OR = 2.24, 95% CI (1.38, 3.63)] are risk factors for the development of osteonecrosis in patients with SLE.ConclusionThe current study found that younger age, hypertension, diabetes, arthritis, Raynaud’s phenomenon, and cyclophosphamide use are independent risk factors for the development of osteonecrosis in patients with SLE.